Combination of Wastewater Treatment Measures and Landscape Ecological Design in Traditional Villages Based on Sustainability Theory: A Case Study of Miao Village in Xiangxi, China. Issue 1 (June 2020) - Tang, Yuanqiang; Tang, Yuanxing; Zhang, Mengmiao; Zhao, Jianmin; Liu, Yunguo; Long, Shaoqiu; Xiao, Can; Chen, Yu; He, Shaoyao; Yang, Chunping
Abstract: The aim of protecting traditional villages is to maintain the population; thus, these villages must be suitable for living. A prerequisite for the liveability of traditional villages is treatment of point and non-point sources of pollution to improve the ecological value of the village. The combination of water pollution control measures and landscape design improves the aesthetic and ecological sustainability. This article takes China's fourth batch of traditional villages, Xiangxi Wengcao Miao Village, as an example. Interviews, field surveys and various discussions were conducted, and the study believes that by connecting the various sewage outlets, they are collected in the first, second and third levels. Treatment ponds (tanks) transformed curved rice fields into secondary treatment tanks and stabilised ponds. Native plants were classified before stable and treatment ponds were excavated. Submerged, floating and emergent plants were artificially planted in the water, and medicinal plants were cultivated around the pond and banks of the creek. These biomass plants are relatively large for the nutrition in the wastewater. Adsorption and digestion of the substance can not only reduce the direct discharge of sewage to downstream regions but also beautify the landscape of the sewage treatment facility.